A Review of the OECD Income Distribution Database - Leonardo Gasparini; Leopoldo Tornarolli (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2014)
In this review we expose the OECD Income Distribution Database to critical scrutiny, identifying its strengths and weaknesses. As it is almost inevitable in any critical assessment, we could not avoid being somewhat biased toward highlighting the limitations, without being similarly emphatic about the virtues of the database. To partly compensate for this asymmetry, we should make clear from the outset that this database is a remarkable undertaking that greatly contributes to the study of income inequality in the OECD countries and that deserves full praise for allowing researchers free and easy access to the data. The following comments should then be read bearing always in mind this positive assessment.
Keywords: 330